Angiotensin II receptor blocker and long-acting calcium channel blocker combination therapy decreases urinary albumin excretion while maintaining glomerular filtration rate - Nakagawa, Naoki; Fujino, Takayuki; Kabara, Maki; Matsuki, Motoki; Chinda, Junko; Kikuchi, Kenjiro; Hasebe, Naoyuki (Hypertension research, 2011)
Microalbuminuria is a recognized risk factor and predictor for cardiovascular events in patients with hypertension. We analyzed changes in hypotensive effect, urinary albumin excretion (UAE) and estimated glomerular filtration rate (eGFR) in subjects with hypertension and microalbuminuria as a subanalysis of the results of the Nifedipine and Candesartan Combination (NICE-Combi) Study. A total of 86 subjects with essential hypertension with microalbuminuria (UAE <300 mg g −1 creatinine) were randomly assigned in a double-blind manner to a combination therapy group (standard-dose candesartan at 8 mg per day plus controlled-release (CR) nifedipine 20 mg per day) ( n =42) or an up-titrated monotherapy group (candesartan 12 mg per day) ( n =44) for 8 weeks of continuous treatment after initially receiving standard-dose candesartan (8 mg per day) monotherapy for 8 weeks (initial treatment). After 8weeks, blood pressure (BP) was significantly reduced in both groups compared with at the end of initial treatment. UAE also showed a significant decrease in the combination therapy group, while there was no significant change of eGFR in either group. A significant positive correlation was seen between BP reduction and UAE after 8 weeks of double-blind treatment in both groups, whereas no significant association was found between ΔUAE and ΔeGFR in either group. These findings show that combination therapy with standard-dose candesartan and nifedipine CR is more effective than up-titrated candesartan monotherapy for reducing BP and improving UAE while maintaining eGFR, and strongly suggest that the combination of an angiotensin II receptor blocker and long-acting calcium channel blocker is beneficial in patients with hypertension and microalbuminuria.